Դարձյալ արևմտահայերենի այբուբենի համակարգում ու ձայնավորը տառի կարգավիճակի արժանացնելու մասին - Անժել Քյուրքչյան (ՀՀ ԳԱԱ հրատ.)
Некоторые гласные и дифтонги периода создания месропова алфавита в ходе общего исторического изменения звуков претерпели артикуляционные изменения, вследствие чего некоторые гласные в начале слова потеряли значение гласного, а дифтонги стали простыми гласными звуками. Since its creation, the phonological system of the Mesropian alphabet, by way of general historical alternation, has undergone changes. As a result, certain front vowels lost their value as such and certain diphthongs turned into simple vowel sounds.
Keywords: Philology; Linguistics; Language and Literature